(untitled) (Journal of Economic Research & Business Administration, 2015)
The article discusses ways to regulate the management of customer relationship in the Republic of Kazakhstan leasing. Proposed share key elements of the management system of leasing relations into two groups: objects of leasing relations and subjects of leasing relations. Offering 3 levels of government leasing relationships in RK.